Utilização digestiva de dietas semi simplificadas com fenos enriquecidos com vinhaça para coelhos em crescimento - Camila Campos Gondim Martins Coelho (2010)
The aims of this study were to evaluate the influence of two qualities of Tifton 85 hay supplemented or not with simplified semi vinasse in diets for growing rabbits of New Zealand White on apparent digestibility of nutrients, the chemical composition of cecotrophes, the nutritional benefits cecotrophes of the performance, carcass yield, the yield of edible offal (liver, kidneys and heart) and the income of the gastrointestinal tract and caecum filled. The diets containing Tifton 85 hay with inclusion level of 53.61% for diet SUP and SUPV and 50.06% for diets INF and INFV. Diets were SUPV and INFV stillage in natura in the proportion of 2:1 (two parts of vinasse to a part of hay). The digestibility trial was conductedwith 40 animals (10 animals per treatment), aged 55 days. The results showed that diets based on simplified semi Tifton 85 hay were not affected by the quality of the hay and the addition of vinasse for the parameters evaluated except for the digestibility of the mineral matter. Forthis variable, animals fed diet INF higher than those obtained from the diet and the animals INFV diet SUP and SUPV had intermediate values. In the experiment caecotrophy eight animals were used per treatment with 66 days of age. In each animal was collared circular timber for 24 hours to prevent the consumption of cecotrophes. The harvest was performed every two hours aiming at the construction of the production curve cecotrophes. The curves showed two peaks of production (diet INFV and SUPV) cecotrophes instead of a (diet SUP and INF), despite the results, production, chemical composition and nutritional benefits havenot changed. In the performance experiment were used and only 13 animals were evaluated diets SUP and SUPV. The results were similar for average daily intake, daily gain, feed conversion, initial weight, final weight, carcass weight, carcass yield, liver, heart yield, yield of the head, skin income, income gastrointestinal tract and performance of the cecum filled. Only kidney showed yield different results, animals fed diet SUPV had kidney yield superior to the animals fed diet SUP.